The Imposition of the Death Penalty for Drug Dealers in the Perspective of Human Rights - Lestari, Dewi Indah (Faculty of Law Universitas Negeri Semarang, 2021)
Law enforcement is doing efforts to the enforcement process or the functioning of legal norms significantly as a code of conduct in traffic or legal relationships in the life of society and state. One way to enforce fair laws is to give the maximum sanctions to perpetrators of serious criminal offenses such as the imposition of the death penalty for drug dealers as listed in Act No. 35 of 2009. However, there are many pros and cons about this death penalty. Highlights of the death penalty usually associated with injustice because it violates human rights, namely the right to life. This paper is to study it from the point of sociology of law, especially the theory of justice. In the perspective of sociology of law, a criminal prosecution devices should include two things: first, it must accommodate public aspirations repay as pondering on the basis of an error rate of the offender. Second, it should include the purpose of punishment, namely to maintain and preserve the unity of the community. Thus, the law should represent the public sense of justice.